To be continued ... : soap operas around the world - Allen, Robert Clyde, 1950- (Comedia., 1995)
To Be Continued ... explores the world's most popular form of television drama; the soap opera. From Denver to Delhi, Moscow to Manchester, audiences eagerly await the next episode of As the World Turns, The Rich Also Weep or Eastenders. But the popularity of soap operas in Britain and the US pales in comparison to the role that they play in media cultures in other parts of the world. To Be Continued ... investigates both the cultural specificity of television soap operas and their reception in other cultures, covering soap production and soap.